The role and expression of miR-100 and miR-203 profile as prognostic markers in epithelial ovarian cancer - Azizmohammadi, Susan (Am J Transl Res, 2016)
Purpose: The present study was aimed to evaluate the clinical significance of miR-100 and miR-203 in epithelial ovarian cancer (EOC) patients. Methods: The expression levels of miR-100/203 in EOC tissue and adjacent non-cancerous samples were determined by real-time RT-PCR. Associations between miRNAs expressions and various clinicopathological characteristics were analyzed. Survival rate was determined with Kaplan-Meier and statistically analyzed with the log-rank method between groups. Survival data were evaluated through multivariate. Cox regression analysis. Findings: Our findings showed that miR-100 was significantly down-regulated in EOC tissue specimens than in adjacent non-cancerous tissues. The expression level of miR-203 was significantly higher in EOC tissues compared to adjacent non-cancerous tissues. Decreased expression of miR-100 was strongly associated with high FIGO stage (P=0.012). The high expression of miR-203 was significantly correlated with advanced FIGO stage (p=0.006), advanced histological grade (p=0.03). Kaplan-Meier analysis and log-rank test have suggested that EOC patients with down-regulated miR-100 expression and up-regulated miR-203 expression have shorter overall survival when compared with patients with other expression groups (log-rank test P<0.001). Multivariate Cox proportional hazards model indicated that the status of miR-100 and miR-203 expression levels were independent predictor of overall survival in patients with EOC. Conclusion: Decreased expression and increased expression of miR-100 and miR-203 may be correlated with progression and poor prognosis of EOC.